2005
DOI: 10.1074/jbc.m411786200
|View full text |Cite
|
Sign up to set email alerts
|

UTP Induces Osteopontin Expression through a Coordinate Action of NFκB, Activator Protein-1, and Upstream Stimulatory Factor in Arterial Smooth Muscle Cells

Abstract: Osteopontin (OPN) is an important chemokinetic agent for several cell types. Our earlier studies have shown that its expression is essential for uridine triphosphate (UTP)-mediated migration of vascular smooth muscle cells. We demonstrated previously that the activation of an AP-1 binding site located 76 bp upstream of the transcription start in the rat OPN promoter is involved in the induction of OPN expression. In this work, using a luciferase promoter deletion assay, we identified a new region of the rat OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 47 publications
(43 reference statements)
2
35
0
Order By: Relevance
“…[31][32][33][34] Although there are only a few reports on Aldo-induced OPN production, Irita et al 21 reported the involvement of activator protein-1 and nuclear factor-kB in the Aldo stimulation of rat renal fibroblasts. Contrary to these past investigations, our study revealed that the formation of an Aldo-MR complex and its binding to GRE were pivotal for the upregulation of OPN gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] Although there are only a few reports on Aldo-induced OPN production, Irita et al 21 reported the involvement of activator protein-1 and nuclear factor-kB in the Aldo stimulation of rat renal fibroblasts. Contrary to these past investigations, our study revealed that the formation of an Aldo-MR complex and its binding to GRE were pivotal for the upregulation of OPN gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the temporal regulation of genes by different transcription factors is not well studied. Only one study has reported that UTP stimulates osteopontin expression via coordinated regulation of the NF-B, USF, and AP-1 signaling pathways (31). While NF-B mediates early activation (15 min), USF1/2 and AP-1 mediate late-phase activation (1 h).…”
Section: Discussionmentioning
confidence: 99%
“…21 Moreover, OPN expression is involved in the coordinated regulation of the NFkB, ERK1/2 and AP-1 signaling pathways, which have been found to be involved in various pathologies, including immunological disorders, neoplastic transformation and renal disorders. 22,23 This pleiotropic pattern may explain why OPN is not a good predictor of vascular calcification specifically, despite that its presence was documented in calcified coronary artery plaques. 8,20 OPN is expressed in adipose tissue and in the livers of obese subjects; thus, obesity-induced inflammation may obscure OPN involvement in vascular calcification.…”
Section: Biomarkers Of Vascular Calcification In Normotension E Stępimentioning
confidence: 99%
“…26 This process is regulated by the same pathways that mediate vascular inflammation and endothelial dysfunction. 5,22 It is possible that the role of fibrinogen in vascular calcification is strictly associated with inflammation.…”
Section: Biomarkers Of Vascular Calcification In Normotension E Stępimentioning
confidence: 99%